ANALISIS SEMIOTIKA VISUAL PADA ILUSTRASI SAMPUL MAJALAH TEMPO EDISI â€œJERAT KEDUAâ€: Visual Semiotics Analysis in the Cover Illustration of Tempo Magazine's â€˜Jerat Keduaâ€™ Edition - Azhar Natsir Ahdiyat; Acep Iwan Saidi; Agus Sachari (Jurnal Dimensi Seni Rupa dan Desain, 2023)
The e-KTP megacorruption case in 2017 that dragged Setya Novanto made it a public conversation, including mass media like Tempo Magazine on its cover. Tempo Magazine uses illustrated images in each of its releases with distinctive characters and styles and often creates controversy. In addition, the illustrations on this cover also have various hidden meanings and codes that need to be interpreted deeply. Therefore, this study aims to explain the structure of the visual signs on the cover illustration of the â€œJerat Duaâ€ edition of Tempo Magazine. In addition, this research is also intended to reveal the codes contained in the cover illustration. This study uses a qualitative approach with an interpretive descriptive analysis. The method is visual semiotics with Roland Barthes' semiotics theory, including the structure of visual signs and the Five Codes of Barthes. The researcher concludes that the structure of the â€œJerat Duaâ€ edition of Tempo Magazine is composed from denotative signifier which change its meaning to connotative signified. The connotative meaning that appears is based on a convention, the anchoring of meaning, gestures/expressions, the use of metaphor/metonymy rhetoric, and references from reality. The codes that are revealed on the cover of this magazine include hermeneutic, semantic, proairetic, symbolic, and cultural codes. Keywords: illustration, magazine cover, visual semiotic, sign, code